Bila Dua Sudut Pandang Bertemu: Suatu Kasus dalam Pertunjukan Gamelan - Santosa Santosa (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
In attending performances audiences use their woridviews to evaluate and make judgments of the show. Each group of people has different views in which they want to apply to the performances. Two groups of audiences may have conflict when they are present in performances. This paper examines how and why the two views â€œcompete withâ€ one another to fit their taste